1998
DOI: 10.1103/physrevb.58.9933
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-size effects on radiative lifetimes and relaxation of excitons in semiconductor nanostructures

Abstract: A systematic study of exciton dynamics is presented in quantum boxes formed naturally along the axis of a V-shaped quantum wire, by means of time and spatially resolved resonant photoluminescence. The dependence of radiative lifetimes and relaxation mechanisms of excitons is determined versus the size of the boxes. The radiative recombination rate varies linearly with the length of the box, showing that the exciton has a coherence volume equal to the volume of the box. In a low excitation regime, emission from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 54 publications
10
76
0
Order By: Relevance
“…The decay time of localized excitons is inversely proportional to the coherence volume of the exciton, 15) which in the present case is given by the volume of the localization centre. 16) Consequently, as the QW thickness is constant across the sample, we attribute the variation in loc to local change in the spatial extension of exciton localization centres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decay time of localized excitons is inversely proportional to the coherence volume of the exciton, 15) which in the present case is given by the volume of the localization centre. 16) Consequently, as the QW thickness is constant across the sample, we attribute the variation in loc to local change in the spatial extension of exciton localization centres.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, since we do not observe any change in QW emission linewidth when scanning across a sample of given QW thickness, we assume that E loc is constant along the QW plane. Regarding loc , it only depends on the coherence volume of the localized exciton 15,16) and we take it to be constant with temperature. In contrast, r depends on M and on the oscillator strength f osc , and increases linearly with temperature, due to the population of states lying out of the light cone (i.e., exciton states that do not couple to light).…”
Section: Resultsmentioning
confidence: 99%
“…For larger QDs, i.e., in the weak confinement regime, the exciton lifetime is known to be inversely proportional to the QD volume. 26 Indeed, in this case substituting Eq. (4) into Eq.…”
Section: ͑4͒mentioning
confidence: 99%
“…Spin relaxation would remain an issue, but a recent experimental result shows that the 1X spin decoherence time T 2 can be much longer than the radiative lifetime in CdSe quantum dots [19]. Alternatively, one could reduce τ rad , either by using larger quantum dots [28], or by placing the 1X state on resonance with a microcavity [29]. It has already been demonstrated that the spontaneous emission rates of quantum dots can be enhanced by a factor of up to 5 in pillar microcavities [30].…”
mentioning
confidence: 99%